Thinking Inertia and Path Dependence in US Chip Hegemony Strategy - Jin, Zuoping (Transactions on Economics, Business and Management Research, 2024)
As human society steps into the digital era, the chip industry has increasingly become a strategic place for national security, economic development, scientific and technological progress, as well as global political games. Although the US has long dominated the chip industry, China’s recent explosive growth in the semiconductor sector poses a serious threat to US technical superiority. Consequently, the chip race has taken center stage in the ongoing Sino-US technology rivalry. By observing the U.S. policy documents and diplomatic practices related to chip strategy, we can find that the U.S. in the process of maintaining and advancing its chip hegemony presents technological hegemony, industrial protectionism, pseudo-multilateralism thinking inertia, unilateral export control, industrial policy support, as well as multilateral alliance construction of the path of dependence.